2007
DOI: 10.1021/jm061082q
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Potent Histone Deacetylase Inhibitor

Abstract: Histone deacetylase (HDAC) inhibitors have potential for cancer therapy. An HDAC inhibitor based on a cyclic peptide mimic of known structure, linked by an aliphatic chain to a hydroxamic acid, was designed and synthesized. The chimeric compound showed potent competitive inhibition of nuclear HDACs, with an IC50 value of 46 nM and a Ki value of 13.7 nM. The designed inhibitor showed 4-fold selectivity for HDAC1 (57 nM) over HDAC8 (231 nM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…FK-228 is a prodrug of an active agent, red FK. Among newer HDACi is a cyclic peptide mimic linked by an aliphatic chain to a hydroxamic acid, which is active at millimolar concentrations (59).…”
Section: Hdaci: Chemistrymentioning
confidence: 99%
“…FK-228 is a prodrug of an active agent, red FK. Among newer HDACi is a cyclic peptide mimic linked by an aliphatic chain to a hydroxamic acid, which is active at millimolar concentrations (59).…”
Section: Hdaci: Chemistrymentioning
confidence: 99%
“…A variety of studies were reported in the meantime where structure-based optimization of HDAC inhibitors was successfully guided by docking the compounds into the HDLP active site. [18][19][20][21][22][23][24][25][26][27][28] In the case of HDAC1 and HDAC6 a crystal structure of the enzyme is yet to be elucidated and in its absence, homology models of HDAC-1 and HDAC-6 complexed with hydroxamate based inhibitors were generated by several groups. [29][30][31][32][33][34][35][36][37][38][39][40] The refined models were generally checked for structural integrity using molecular dynamics simulations and various protein structure checking tools.…”
Section: Docking Studies Using X-ray Structures and Homology Modelsmentioning
confidence: 99%
“…Rigidity is an important feature for the inhibitory activity of compound 60, as demonstrated by its acyclic derivative compound 61 (Fig. (5)), which was 176-fold less active in HeLa nuclear extracts [102].…”
Section: Cyclic Peptidesmentioning
confidence: 99%